A 8-week periodized mesocycle leading to a national level weightlifting competition - Pistilli, E. E.; Kaminsky, D. E.; Totten, L.; Miller, D. (Strength and Conditioning Journal, 2004)
The concepts of periodization are often applied to the training programs of athletes in order to prepare for competition. These concepts include manipulation of training variables such as volume load, training intensity, and exercise selection. The following training program is one example of how these concepts can be manipulated and applied to the sport of weightlifting.